Performance-level indicators of male elite handball teams - Almeida, A. G.; Merlin, M.; Pinto, A.; Torres, R. D. S.; Cunha, S. A. (International Journal of Performance Analysis in Sport, 2020)
The aim of this study was to identify the most relevant variables to characterise the performance level of the teams through Men`s World Championships (2007-2019). Forty-seven attributes from match-related statistics and characteristics of players were analysed in 168 participant teams. Descriptive discriminant analysis classified correctly 69.6% of the cases and selected the height of players, 9-m efficiency, international matches disputed, wing efficiency, blocked shots, 7-m goalkeeper efficiency and 2-min suspensions which were the most relevant indicators. Top-Elite was significantly different (one-way ANOVA) from Middle- and Low-Elite in all variables selected, except for 7-m goalkeeper efficiency. Linear regression shows that wing efficiency and blocked shots were the only variables with a tendency of changes through seven editions. The best teams have the tallest players and with more international matches disputed, were most efficient in 9-m and wing finalisations and block more shots in defence. These findings may guide scientists and sports trainers to select players, prescribe training procedures, analyse opponents and establish match strategies with special attention to these variables.